The Impact of Kahoot Learning Media on Tenth Grade Students' Learning Outcomes in Telecommunication Systems at SMK Telkom School Jakarta, Investigated by Learning Independence Levels - Alfi Manarulhuda Hanafiah; Bagus Dwi Cahyono; Irwanto Irwanto (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study analyzes the influence of Kahoot learning media on the cognitive learning outcomes of Class X students in Telecommunication Systems subject at SMK Telkom School Jakarta, considering their level of learning independence. Employing a quantitative approach with a quasi-experimental method, the research found that the cognitive learning outcomes of students who used Kahoot media (average 77.33) were significantly higher than those using PowerPoint media (average 62.59). Furthermore, students with a high level of learning independence (average 77.33) achieved significantly higher cognitive learning outcomes than those with a low level (average 69.85). A significant interaction was also observed between the type of learning media (Kahoot and PowerPoint) and students' learning independence level concerning their cognitive learning outcomes. These findings lead to the conclusion that Kahoot learning media is effective in improving students' cognitive learning outcomes and learning independence.